The physics of medical imaging [ - Chua, Eu-Hua; Egan, Tim , 1957-; Swain, Tiki (VEA (Video Education America), 2009)
"Technological advances developed from our understanding of the electromagnetic spectrum, has provided medical technologists sophisticated tools with which to analyze and interpret bodily process for diagnostic purposes.These methods are usually non-invasive processes for identifying and monitoring diseases or injuries of the body by using images representing internal anatomical structures and organs of the body. "--Container